If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + 2(x + 3) = 11 Reorder the terms: 5 + 2(3 + x) = 11 5 + (3 * 2 + x * 2) = 11 5 + (6 + 2x) = 11 Combine like terms: 5 + 6 = 11 11 + 2x = 11 Add '-11' to each side of the equation. 11 + -11 + 2x = 11 + -11 Combine like terms: 11 + -11 = 0 0 + 2x = 11 + -11 2x = 11 + -11 Combine like terms: 11 + -11 = 0 2x = 0 Solving 2x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '2'. x = 0 Simplifying x = 0
| y=-3.5-4.5 | | 3x-5(-x-17)=181 | | 198=5x+3(-7+2) | | 36/x=30/42 | | n/125=4/100 | | (4x)(-3xy^2)=-12x^2y^2 | | 45t+9= | | x=16+-0.4y | | 4c+19c+19=-20+20c | | 7x-2=5x-3+2x+1 | | c=1/2e*m | | .25x+.10y=4 | | 686=7(-8x-22) | | -3-16b=-3-15b-2b | | -x+6=y | | (3x-5)+(7y)=180 | | 6y=-2+3x | | -18w-17=19-20w | | 7x-2=5x-3+2x-1 | | -2*10-3y=-7 | | 17=3x-2(x-5) | | 2p+2p-3=2p+1 | | -20-6k=-k | | 3x-x+2=22 | | 2x^(1/2) | | 27=y/3-13 | | -2*3-3y=-7 | | 4w-22=8w-70 | | 4x+8x^2=9 | | -17g-4=14-8g | | log(45/x)=0.34 | | -96=-6g+2g |